2011
DOI: 10.1177/1077546311404267
|View full text |Cite
|
Sign up to set email alerts
|

Vibration control of Timoshenko beam traversed by moving vehicle using optimized tuned mass damper

Abstract: The dynamic behavior of a combined bridge–vehicle system in which the bridge is modeled as a Timoshenko beam and the vehicle as a half-car planar model is investigated using the finite element method. The governing equations of motion of the Timoshenko beam with the attached tuned mass damper (TMD) traversed by a moving vehicle are obtained. Adesign optimization algorithm is developed in which the analysis module based on the derived finite element formulation has been combined with the optimization module usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The goal is to find an optimized design for the tuned mass damper attached to the Timoshenko beam traversed by moving vehicle that solved in Ref. [17]. Table 5 presents the optimal values of the TMD after performing the optimization in AYSYS © , based on the flowchart illustrated in Fig.…”
Section: Optimization Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal is to find an optimized design for the tuned mass damper attached to the Timoshenko beam traversed by moving vehicle that solved in Ref. [17]. Table 5 presents the optimal values of the TMD after performing the optimization in AYSYS © , based on the flowchart illustrated in Fig.…”
Section: Optimization Proceduresmentioning
confidence: 99%
“…Since all the parameters of the TMD, i.e., the absorber mass, spring stiffness and the damper coefficient, are involved in the presented non-dimensional parameters, one may consider the non-dimensional parameters as the design variables for the optimization problem. Therefore, the optimization problem can be described as [3,17] Design variables:…”
Section: Optimization Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2010) developed a numerical method to analyze coupled railway vehicle-bridge systems of non-linear features. Moghaddas et al (2012) studied the dynamic behavior of bridge-vehicle system attached with TMD, using the finite-element method. It was shown that by attaching an optimized TMD to a bridge, a significantly faster response reduction can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The modal method [15] relies on the eigenvalue problem that is not easily for damaged structures. On the other hand, the FEM [16,17] requires a time consumable task to identify position of moving load for computing nodal load. Moreover, both the methods are poorly applicable for evaluating the shear force [18] and high frequency components [19].…”
Section: Introductionmentioning
confidence: 99%